Latvian Teachers’ Perspectives on Early Childhood Educational Practice - Ozola, Aija (European Journal of Social Science Education and Research, 2019)
The Education Law of Latvia recognizes early childhood education as an educational level in which multi-dimensional development of the child as an individual, strengthening of health and preparation for the acquisition of primary education takes place. Currently, early childhood education is undergoing considerable transformations and transition to a competence-based approach. Teachers’ perspectives serve as significant indicators for analysis of current educational situation and therefore highlight the core areas for enhancing early childhood educational practice. The design of the study is based on qualitative research using data from a survey and focus group discussions. The aim of the study is to identify and analyse teachers’ perspectives on early childhood educational practice. In accordance to the aim, the following research questions were posed: (1) what is early childhood teachers’ personal meaning of good educational practice; (2) what factors could contribute to enhance the early childhood educational practice in future? To identify teachers’ perspectives, a survey was conducted with early childhood teachers implementing curriculum in municipal early childhood education institutions around Latvia. The answers to two open-ended questions as a part of a larger questionnaire were analysed. The in-depth examination of perspectives was reached by implementing several focus group discussions. Data were analysed using the method of qualitative content analysis. The findings revealed wide diversity in teachers’ personal meaning of good educational practice. The issues related to developmental psychology-based learning outcomes and school-readiness still dominate among teachers’ perspectives. Postmodern views on a child emphasizing children’s diversity and uniqueness were often mentioned as well. The factors contributing to good educational practice were categorized into four main areas such as organization of the pedagogical process, teachers’ competences, environment of an early childhood setting, collaboration with parents. In general, Latvian teachers’ perspectives demonstrate readiness for transition to a competence-based approach in early childhood education. However, identified contributing and hindering factors should be taken into account during the process of transformations.